Factors Associated with Short Hospital Stay After Combined Middle Meningeal Artery Embolization and Surgical Evacuation for Chronic Subdural Hematoma - Anthony Terraciano; Bluyé DeMessie; Muhammed Amir Essibayi; Abdulrhman Alsalama; Khushal Gupta; Hamza Adel Salim; Alireza Karandish; Nimer Adeeb; Dhairya A. Lakhani; Yan-Lin Li; Diego Alejandro Ortega; Joseph Carnevale; et al. (Clinical Neuroradiology, 2026)
Abstract Background Middle meningeal artery embolization (MMAE) plus surgical evacuation is increasingly used for chronic subdural hematoma (cSDH), but predictors of length of stay (LOS) and outcomes associated with early discharge remain unclear. Methods We performed a multicenter MESH Registry study (2019–2024) of patients undergoing MMAE and surgical evacuation for symptomatic cSDH. Short-stay discharge was defined as LOS ≤4 days. Predictors were identified using multivariable logistic regression. The 90-day composite adverse event was defined as cSDH recurrence requiring intervention, reintervention (repeat MMAE or surgical evacuation), or 30-day all-cause readmission. Safety was assessed using adjusted logistic regression, generalized estimating equations (GEE), inverse probability of treatment weighting (IPTW), and multiple imputation by chained equations (MICE). Results Among 647 patients (mean age 72.6 years; 74.0% male), 156 (24.1%) had short-stay discharge. Median LOS was 8 days (IQR 5–15). Older age (aOR 0.76 per 10 years; 95% CI 0.62–0.93; P = 0.008), higher baseline modified Rankin Scale score (aOR 0.79 per point; 95% CI 0.67–0.94; P = 0.007), and greater midline shift (aOR 0.90 per mm; 95% CI 0.85–0.96; P = 0.001) were independently associated with lower odds of short-stay discharge. C‑statistic was 0.683. The 90-day composite event rate was 17.1% in short-stay versus 23.7% in long-stay patients. Short-stay discharge was not significantly associated with the composite outcome on adjusted analysis (aOR 0.56; 95% CI 0.30–1.07; P = 0.08), GEE (aOR 0.61; 95% CI 0.33–1.12; P = 0.11), or MICE (aOR 0.74; 95% CI 0.44–1.25; P = 0.26). IPTW showed a discordant association (OR 0.47; 95% CI 0.24–0.92; P = 0.03). Conclusions Older age, worse baseline function, and midline shift were associated with longer hospitalization. Short-stay discharge was not associated with a statistically significant increase in adverse-event rates; however, the study was not powered to establish non-inferiority or safety equivalence, and clinically meaningful differences cannot be excluded.